Effects of Different Methionine Levels in Low Protein Diets on Production Performance, Reproductive System, Metabolism, and Gut Microbiota in Laying Hens - Ma, Miaolin; Geng, Shunju; Liu, Meiling; Zhao, Lihong; Zhang, Jianyun; Huang, Shimeng; Ma, Qiugang (Frontiers in Nutrition, 2021)
This study investigated the effects of different levels of methionine (Met) in a low protein diet on performance, reproductive system, metabolism and gut microbial composition of laying hens, to reveal the underlying molecular mechanism of Met in a low protein diet on the host metabolism and gut microbial composition and function of hens. A total of 360 healthy 38-week-old Peking Pink laying hens with similar body condition and egg production (EP) were randomly divided into four groups with nine replicates per treatment and ten hens per replicate. Hens in each treatment group were fed low protein diets containing different levels of Met (0.25%, 0.31%, 0.38% and 0.47%, respectively) for twelve weeks. Feed and water were provided ad libitum throughout the trial period. The results showed that, compared with the 0.25% Met group, final body weight (FBW), average daily gain (ADG), EP, egg weight (EW), and average daily feed intake (ADFI) in the other groups were significantly increased and feed egg ratio (FER) was decreased. Meanwhile, EW, yield of abdominal fat (AFY) in 0.47% Met group was higher than those in other groups. Triglyceride (TG), Estradiol (E2), total protein (TP), albumin (ALB) and immunoglobulin A (IgA) in 0.38% and 0.47% Met groups were higher than those in other groups. In addition, 16S rRNA gene sequencing revealed that there was no difference in Sobs index, ACE index, and Shannon index among all groups. However, it is worth noting that feeding low protein diets with Met changed the gut microbial composition (e.g., the supplementation of Met increased the level of Lactobacillus and decreased the proportion of Faecalibacterium). Also, our results showed that the changes of gut microbial composition induced by the diets with different levels of Met were closely related to the changes of key parameters: ADFI, EW, FBW, TG, EM, EP, ADG, FER and uric acid (UA). In conclusion, this study suggested that when the Met level was about 0.38 0.47%, the performance of the laying hens was optimal. Also, our results highlight the role of adding an appropriate amount of Met to the low protein diet in laying hens.